Income tax noncompliance in Germany, 2001-2014 - Hannes Fauser; Sarah Godar (Freie Universität Berlin, School of Business & Economics, 2021)
This paper estimates income tax underreporting for the case of Germany, by income category and along the income distribution. Comparing weighted samples of survey and tax data, we find patterns that are in line with the literature: Average income from self-employment and from rent and lease in the survey is higher than in the tax data, increasing in upper quintiles. Income underreporting to the tax authorities may be one of several possible explanations for these descriptive findings. We therefore expand our analysis with the Pissarides & Weber (1989) approach that has been applied to a range of countries and data sources before. We use the German Socioeconomic Panel and the Taxpayer Panel, estimating food, housing cost and donation regressions. Results indicate that self-employment is associated with higher housing cost but not with higher food expenditure in the SOEP. In the TPP we find more robust indication of underreporting as self-employment and business incomes are significantly associated with higher donations and even more so for the top-income decile. We use our results to derive tentative estimates of aggregate tax revenue losses due to underreporting of self-employment and other non-wage incomes.
urn:nbn:de:kobv:188-refubium-32860-6
Keywords: D12; D31; H24; H26; 330; tax evasion; income misreporting; personal income tax; self-employment; distributional effects